2006
DOI: 10.1007/s11064-006-9065-3
|View full text |Cite
|
Sign up to set email alerts
|

Malathion-induced Oxidative Stress in Rat Brain Regions

Abstract: Malathion is a pesticide with high potential for human exposure. However, it is possible that during the malathion metabolism, there is generation of reactive oxygen species (ROS) and malathion may produce oxidative stress in intoxicated rats. The present study was therefore undertaken to determine malathion-induced lipid peroxidation (LPO), protein carbonylation and to determine whether malathion intoxication alters the antioxidant system in brain rats. Malathion was administered intraperitoneally in the acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 23 publications
(34 reference statements)
5
75
1
Order By: Relevance
“…¥ P \ 0.05 [3,[23][24][25] corroborate our findings. From this study it is clear that neonatal and juvenile rats are at higher risk than the young adult because of relative deficiency of enzymatic and non-enzymatic antioxidants.…”
Section: Discussionsupporting
confidence: 87%
“…¥ P \ 0.05 [3,[23][24][25] corroborate our findings. From this study it is clear that neonatal and juvenile rats are at higher risk than the young adult because of relative deficiency of enzymatic and non-enzymatic antioxidants.…”
Section: Discussionsupporting
confidence: 87%
“…In humans, Banerjee et al (1999) observed increased levels of LPO and ROS scavenging enzymes in blood samples of OP-poisoned subjects, and Ranjbar et al (2002) reported increased levels of erythrocyte LPO and reduced anti-oxidant capacity in OP pesticide manufacturing workers. In vitro exposure to chlorpyrifos resulted in the induction of erythrocyte LPO (Gultekin et al, 2000); while Sharma et al (2005) reported that dimethoate exposure in rats increased the generation of free radicals in liver and brain, and Fortunato et al (2006) showed that LPO in brain increased after acute malathion exposure in rats. Finally, Debnath and Mandal (2000) observed that quinalphos caused damage and degeneration of testicular tissue in rats due to free-radical mediated LPO.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that OP produce oxidative stress in different tissues, such as liver, blood and brain (Akhgari et al, 2003;Sharma et al, 2005;Fortunato et al, 2006) through the formation of reactive oxygen species (ROS) (Banerjee et al, 1999;Ranjbar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that LPO is accompanied by an alteration (inhibition or activation) in the antioxidant defence systemin different organs following acute, sub chronic and chronic exposure to OP compounds. 5 Nevertheless, recent evidence suggests that exposure to different stress models and concentrations (acute, repeated and chronic restraint stress) have an important implication in the alteration of the antioxidant defence system. 6 The liver is the major metabolizing and the most active organ for mediating bio-activation of thiono-organophosphates.…”
Section: Introductionmentioning
confidence: 99%